Long-term safety and drug survival of acitretin in psoriasis: a retrospective observational study - Leena Chularojanamontri (2020)
© 2018 The International Society of Dermatology Background: This retrospective observational study aimed to investigate the long-term safety, drug survival, and factors associated with the survival of acitretin in a real-world setting. Methods: Data of adult patients with psoriasis who attended Siriraj Hospital between 2012 and 2017 and were treated with acitretin were reviewed. Demographic data and clinical courses were recorded. The Kaplan–Meier curve and Cox regression were used to calculate drug survival and the factors associated with drug survival, respectively. Results: Of 104 patients, 56 and 48 were male and female, respectively, with a mean treatment duration of 3.2 years. The mean cumulative dose per patient was 19.28 ± 7.84 mg/day. Acitretin was administered to 73, 39, 24, and six patients for more than 1, 3, 5, and 10 years, respectively. Most side effects were mild and tolerable; only nine patients withdrew acitretin due to side effects. No patients developed clinical features of cirrhosis or uncontrolled hyperlipidemia. The drug survival rates were 79%, 69.5%, 61.2%, 57.6%, and 53.5% at 1, 2, 3, 4, and 5 years, respectively, higher than those of previous studies. Patients without obesity, metabolic syndrome, and dyslipidemia did not have a significantly longer acitretin survival compared to patients with these comorbidities. Conclusions: Long-term, low-dose acitretin in patients with psoriasis is unlikely to cause significant liver or lipid problems. In countries with difficulty accessing biological agents for psoriasis, acitretin may have a high drug survival rate due to its long-term safety. This study has several limitations: its retrospective nature, single-center study design, and small sample size.